Polyvictimization, Sex Work, and Depressive Symptoms Among Transgender Women and Men Who Have Sex With Men - Srivastava, Ankur (Journal of interpersonal violence, 2022)
This article examined the association among polyvictimization, sex work, and depressive symptomology among transgender women and men who have sex with men (MSM) in India. Data comes from a cross-sectional epidemiological study with 1,366 transgender women (from three states) and 2,182 MSM participants from five states of India. Multivariate regressions were used to examine how polyvictimization and sex work are associated with depressive symptoms. In total, 70% of transgender women and 44% of MSM participants in the sample reported being in sex work; 30% of transgender women and 17% of MSM reported at least one experience of abuse in last 6 months. In bivariate analysis, transgender women in sex work were more likely to report sexual abuse, and MSM in sex work more likely to report all types of abuse (physical, sexual, verbal, and property), compared to their peers. In multivariate models (with transgender women and MSM), increase in endorsement on types of abuses (polyvictimization) and being in sex work were associated with higher odds of reporting depressive symptoms. Both models controlled for age and marital status, while the model with transgender women also controlled for gender transitioning, and the model with MSM controlled for identity typology. National intervention program on HIV risk reduction must prioritize victimization screening and crisis management as part of their work. In addition, the interventions must be responsive to the diversity of the population, including those who engage in sex work, and address issues of access and support to gender transitioning services, and focus on psychosocial interventions to reduce stress due to gender-based stigma and discrimination among transgender women and MSM.